Genetic Relationships in Tylophora Species of Goa as Revealed by Simple Sequence Repeats (SSR) and Inter Simple Sequence Repeats (ISSR) Pooled with Random Amplification of Polymorphic DNA (RAPD) - UMA MASUR; P. HIMA KUMARI; KAILAS GOKHALE; U.M.X. SANGODKAR (International Journal of Pharma and Bio Sciences, 2018)
Genetic variations of six Tylophora accessions were analyzed using SSR (Simple sequence Repeats) and ISSR (Inter- simple sequence repeats) markers. Above results were pooled with previously done randomly amplified polymorphic DNA (RAPD), which was performed on the same species of Tylophora. Out of six SSR primers used, amplification of band length 110 bp was observed in all plants with SSR primers 1-4. Primers 5 and 6 did not show amplification. During ISSR analysis, amplification of genomic DNA of the 6 accessions by 4 primers generated total 18 scorable bands which were 100% polymorphic in the range of 650- 2000 bp. Earlier reported RAPD analysis using OPF 1-10 primers generated 39 amplification products in the range of 40 to 3000bp. On an average each primer generated 4.875 bands, all polymorphic. Similarity index values ranged from 0.125 to 1 for ISSR and 0 to 0.40 for RAPD. Pooled SSR-ISSR gave total 22 bands and similarity index in the range of 0.263158 to 1 whereas pooled RAPD-SSR and ISSR gave altogether 62 bands and the similarity index in the range of 0.131579 to 0.580645. The results indicated that all the three marker systems were effective in determination of genetic relationships among Tylophora species collected from different places of Goa. It also shows that geographically, isolated individuals tend to accumulate genetic variations during the course of environmental adaptations.